IMPACT OF THE EL NIÑO PHENOMENON 2017 IN THE PIURA REGION - VELÁSQUEZ-HIDALGO, Oswaldo (2024)
The research analyzes the natural phenomenon El Niño, in the context of Change Climate, which increasingly affects both the physical environment as natural and to a greater extent to poorly developed societies such as This is the case of the Peruvian one. It is undeniable that the consequences are even more impactful in this environment due to the lack of contingency plans, the scarcity of resourcesto replace infrastructure and equipment affected and fundamentally due to informality. The overall objective of the research is: Determine the impact of El Niño Costero 2017 on the Piura region. Methodology: the study is of an applied type, exploratory level, non-experimental design, qualitative and quantitative approach; were analyzed statistical instruments from institutions such as the INEI, CENEPRED, among others, at the same time, documentary observation and observation of the phenomena directly. The results show that indeed the Niño Costero 2017 has had a strong impact, compromising agriculture, as well as all activities that affect the quality of life.